Ecommunity Engagement for Innovative Services – Our Story in Prof. Kenneth Dike State Central Elibrary, Awka, Anambra State - Osuigwe, Nkem Ekene (MiddleBelt Journal of Library and Information Science, 2020)
Public libraries need to practice community engagement in order to provide services that address societal issues and emerging needs in their different communities and not just those that are regarded as traditional library and information services. Prof. Kenneth Dike State Central eLibrary, Awka leveraged on the LRCN/IREX interventions in public libraries in Nigeria and exposure to public libraries activities on the continent to assess community needs and introduce innovative services such as job search corner, idea exchange and use of the library as a public community space to pull in partnerships that are working for the good of the community. These have caused an increase in patronage of the library and positively changed the perception the community has about the library.